PGV-1 is a potent antimitotic agent - Barinta Widaryanti; Edy Meiyanto; Muhammad Da'i; Masashi Kawaichi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
Carcinogenesis can be involved in the malfunctioning of programmed cell death Most of the anticancer drug in current use induce apoptosis in susceptible cells. The fact that disparate agent interacting with different targets seem to induce cell death through some common mechanism suggest that anticancer activity is determined by the ability of inhibiting cell growth.Pentagamavunon-1 (PGV-1) is one of the curcumin analogue which showed to have potency in inhibiting proliferation of human breast carcinoma cell T47D. The effect on T47D growth is associated with cell cycle arrest in G2/M phase at the concentration of 2.5 mM, followed by hyperploidy. Our data on polymerization assay, indicate PGV-1 interact with tubulin in different manner from taxol. PGV-1 inhibit tubulin polymerization on cell culture while taxol stabilized tubulin polymerization. Immunostainning data on cell treated with PGV-1 showed slightly tubulin condensation, while cell treated with taxol showed tubulin condensation distinctly at 12 minutes after releasing from depolymerization agent.In conclusion, PGV-1 represent a new microtubule inhibitor and has the potential to be developed for anticancer drugKey words: Pentagamavunon-1, T47D, tubulin, antimitotik